PENGARUH SERVANT LEADERSHIP DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERTANIAN, PERIKANAN DAN KETAHANAN PANGAN KABUPATEN LANDAK - Sudhiarto, Setiawan Jodi Sudhiarto B1021161024 (Jurnal Manajemen Update, 2020)
ABSTRACTThe purpose of this research is to discuss and analyze the influence of servant leadership and work environment on the performance of the employees of the agriculture and fisheries service in the porcupine district. This type of research is a descriptive study with a quantitative approach. The population in this study were employees of the Department of Agriculture, Fisheries and Food Security Landak District. The number of samples is 51 respondents, then the data processing uses multiple linear regression analysis. The results showed that Servant Leadership and the Work Environment had a positive and significant effect on the Performance of Landak District Agriculture, Fisheries and Food Security Employees. The ability of this variable in explaining its effect on Employee Performance is 24.7% while the remaining 75.3% is explained by other factors outside the research modelKeywords: Servant Leadership, Work Envirvonment, Employe Performance.Daftar PustakaAji, M., & Palupiningdyah. (2016). Pengaruh Servant Leadership Terhadap Kinerja Karyawan Dengan Burnout Sebagai Variabel Intervening. Management Analysis Journal, 5 (3).178-188.Dennis, R. (2004). Development of the Servant Leadership Assessment Instrument. Dissertation Abstracts International, 5 (3), 18-57.Dwi Septianto. 2010. Pengaruh Lingkungan Kerja dan Stres kerja terhadap Kinerja Karyawan Studi pada PT. Pataya Raya Semarang. Jurnal Skripsi. Semarang : jurusan manajemen fakultas Ekonomi Universitas DiponegoroGreenleaf, R. K. (1997). Servant Leadership: A journey into the nature of legitimate power and greatness. Mahwah, NJ: Paulist Press.Husein Umar. 2013. Metode Penelitian untuk Skripsi dan Tesis Bisnis EdisiKedua. Jakarta: Rajawali PersKamanjaya, G., Supartha, W., & Dewi, I. G. (2017).Pengaruh Servant Leadership Terhadap Komitmen Organisasi dan Kinerja Pegawai (Studi kasus pada pegawai negeri sipil di RSUD Wangaya Kota Denpasar). E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 6 (7), 17-35.Lestary, Lyta & Harmon (2017), Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Dirgantara Indonesia (Persero) ). Jurnal Riset Bisnis dan Investasi. ISSN:2460-8211.Vol.3, No.2 2017Oktavianus Chandra (2019). Pengaruh Servant Leadership Dan Komitmen Organisasional Terhadap Organizational Citizenship Behaviordan Kinerja Karyawan (Studi Kasus Pada Perusahaan Astra Honda Motor Pattimura).Jurnal Manajemen Update Vol. 8 No. 3 (2019). jurnal.untan.ac.idPrilian. Ni Made Rena, Indrawati. Yayu, & Mandana. I GPB. Sasrawan (2014). Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Di Pt Mitra Global Holiday Jimbaran Bali. Jurnal IPTA | ISSN : 2338-8633 Vol. 2 No. 1, 2014Ramadhan, F.A., Sunoharjo, B.S., & Djudi, M. (2018). Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Variabel Mediator Motivasi Kerja (Studi Pada Karyawan Pg. Kebon Agung Malang). Jurnal Administrasi Bisnis (JAB)|Vol. 63 No. 1 Oktober 2018| administrasibisnis.studentjournal.ub.ac.idSandra, P. A. P., & Suwandana, I. G. M. (2018).Pengaruh Servant Leadership dan Empowerment Terhadap Organizational Citizenship Behaviour Pada Karyawan Asa Villa Seminyak. E-JurnalManajemenUnud, 7 (1), 29-55.Santosa. Fitrah, Adrianto, Syamsir, & Khaidir. Afriva (2019). Pengaruh Servant Leadership Dan Budaya Organisasi Sekolah Terhadap Kinerja Guru Pada Sekolah Menengah Atas Negeri Di Kota Padang. Jurnal Kepemimpinan Dan Pengurusan Sekolah Vol. 4 No. 2, September 2019Sedarmayanti. (2011). Manajemen Sumber Daya Manusia. Bandung: Refika Aditama.Spears. (2010). The Journal of Virtues & Leadership. School of Global Leadership & Entrepreneurship: Regent University, 1 (4), 25-30.Sugiyono. (2016), Metode Penelitian Kuantitatif, Kualitatif dan Kombinasi (Mixed Methode), Bandung: Alfabeta.Sunengsih, N. D. (2014). Pengaruh Lingkungan Kerja, Kepribadian dan Komunikasi Interpersonal Terhadap Komitmen Organisasi Dosen Universitas Persada di Jakarta. Jurnal Manajemen, 18(2), 245-256.Virgiyanti & Sunuharjo, B.S. (2018). Pengaruh Lingkungan Kerja Fisik Dan Non Fisik Terhadap Kinerja Karyawan (Studi Pada Karyawan Divisi Fresh Pt.Trans Retail Indonesia (Carrefour) Plaza Tangerang City). Jurnal Administrasi Bisnis (JAB) | Vol. 61 No.2 Agustus 2018 | administrasibisnis.studentjournal.ub.ac.idWursanto. (2011). Manajemen Sumber Daya Manusia. Yogyakarta: Liberty.